2014
DOI: 10.3109/10715762.2014.968147
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged swimming promotes cellular oxidative stress and p66Shc phosphorylation, but does not induce oxidative stress in mitochondria in the rat heart

Abstract: Exercise-induced changes in p66Shc-dependent signaling pathway are still not fully understood. The p66Shc protein is one of the key players in cell signaling, particularly in response to oxidative stress. Therefore, the aim of this study was to investigate the effect of prolonged swimming on the phosphorylation of p66Shc as well as the induction of mitochondrial and cellular oxidative stress in rat hearts. Male Wistar rats were divided into a sedentary control group and an exercise group. The exercised rats sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…Previous studies have shown that cells and tissues derived from p 66Shc -null mice accumulate significantly less oxidative stress, and the deletion of p 66Shc gene in mice resulted in the decreased formation of mitochondrial H 2 O 2 [ 16 ]. Our finding is also consistent with a latest study demonstrating that a prolonged swimming exercise promoted cellular oxidative stress and p 66Shc phosphorylation in rat heart [ 42 ] and supporting the hypothesis that acute exercise increases H 2 O 2 levels involving upregulating p 66Shc signaling. p 66Shc is a peculiar protein, acting specifically in the mitochondrion as a redox enzyme that generates H 2 O 2 by sequestering electrons from the respiratory chain [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that cells and tissues derived from p 66Shc -null mice accumulate significantly less oxidative stress, and the deletion of p 66Shc gene in mice resulted in the decreased formation of mitochondrial H 2 O 2 [ 16 ]. Our finding is also consistent with a latest study demonstrating that a prolonged swimming exercise promoted cellular oxidative stress and p 66Shc phosphorylation in rat heart [ 42 ] and supporting the hypothesis that acute exercise increases H 2 O 2 levels involving upregulating p 66Shc signaling. p 66Shc is a peculiar protein, acting specifically in the mitochondrion as a redox enzyme that generates H 2 O 2 by sequestering electrons from the respiratory chain [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…Mitochondria from aged hearts demonstrated a greater enrichment of p66Shc (Ljubicic et al , ). Similarly, intense exercise activated p66Shc; in male Wistar rats, swimming for 3 h per day increased p66Shc phosphorylation, surprisingly without a significant increase in either mitochondrial ROS release or mitochondrial oxidative stress markers or the antioxidant enzyme activities (SOD and catalase) (Ziolkowski et al , ). Thus, regular exercise and ageing affect cardiac p66Shc expression and/or activity; however, the question whether such an increase in p66Shc expression and/or activity relates to cardiomyocyte mitochondria or to mitochondria obtained from other cell types (such as fibroblasts) cannot be resolved using whole cardiac homogenates and remains to be answered using isolated cell preparations.…”
Section: P66shc Structure Function and Expressionmentioning
confidence: 99%
“…p66shc plays a key role in the oxidative stress related to kidney, cardiovascular, and lung disease. [16][17][18][19] p66shc deletion (p66shc −/-) in mice is associated with resistance to oxidative stress and a reduction in p53-dependent apoptosis. p66shc −/mice do not develop emphysema after chronic exposure to smoke, 41 and p66shc deficiency prolongs lifespan, decreasing cytoplasmic ROS levels by activating NADPH oxidase (Nox).…”
Section: Discussionmentioning
confidence: 99%
“…13 p66shc has been associated with oxidative stress in kidney, cardiovascular, and lung disease. [16][17][18][19] However, the role played by p66shc during articular cartilage degeneration has not been investigated although chondrocytes exhibit reduced mitochondrial membrane potential. 20 Meanwhile, siRNA-loaded nanoparticles (NPs) for drug delivery in various diseases has been in the spotlight recently.…”
Section: Introductionmentioning
confidence: 99%